Candida palmioleophila candidemia and bacterial co-infection in a 3-month-old infant with biliary atresia - Aboutalebian, Shima; Nikmanesh, Bahram; Mohammadpour, Masoud; Charsizadeh, Arezoo; Mirhendi, Hossein (Frontiers in Cellular and Infection Microbiology, 2023)
Candidemia caused by rare and uncommon Candida species is becoming more prevalent in pediatric healthcare settings, resulting in significant morbidity and mortality. One such species, Candida palmioleophila, is resistant to fluconazole but highly susceptible to echinocandins. Here, we report the first documented case of C. palmioleophila candidemia in Iran that occurred in a male infant with biliary atresia who had been hospitalized for 2 months. The patient’s blood and urine cultures were positive for both yeast and bacterial species. Through DNA sequence analysis, the yeast isolate was identified as C. palmioleophila. In vitro antifungal susceptibility testing of the isolate against amphotericin B, fluconazole, itraconazole, voriconazole, isavuconazole, posaconazole, and nystatin revealed MIC values of 2, 16, 0.25, 0.0625, 0.125, 0.25, and 4 μg/mL, respectively, and minimum effective concentration for caspofungin was 0.031 μg/mL. Despite receiving antibacterial and antifungal therapies, the patient unfortunately expired due to bradycardia and hypoxemia. Proper identification and epidemiological surveillance studies are needed to understand the exact prevalence of these emerging yeast pathogens. Previously reported cases of C. palmioleophila infection, primarily associated with bloodstream infections and catheter-related candidemia, were reviewed.